2006
DOI: 10.1002/ejlt.200500260
|View full text |Cite
|
Sign up to set email alerts
|

Surface bloom on improperly tempered chocolate

Abstract: Surface bloom on improperly tempered chocolateThe surface composition, in terms of sugar and fat content, on untempered and overtempered chocolates was estimated by carefully scraping the surface layer and analyzing fat and sugar melting enthalpies by differential scanning calorimetry. The dull surface of over-tempered chocolate had a fat and sugar composition similar to the initial chocolate mass, whereas the surface bloom formed on untempered chocolate was nearly depleted of fat, containing primarily sugar a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 8 publications
4
41
0
Order By: Relevance
“…Several studies also have shown that an increase in liquid fat content (decrease in SFC) and the presence of TAGSs incompatible with those of the CB, increasing the fat bloom formation markedly on the chocolate surface (Ali et al, 2001; Langevelde et al, 2001;Guthrie et al, 2005;Lonchampt and Hartel, 2006;Smith et al, 2007). Yet, in the case of the CB chocolate, bloom development was higher than EI chocolate samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies also have shown that an increase in liquid fat content (decrease in SFC) and the presence of TAGSs incompatible with those of the CB, increasing the fat bloom formation markedly on the chocolate surface (Ali et al, 2001; Langevelde et al, 2001;Guthrie et al, 2005;Lonchampt and Hartel, 2006;Smith et al, 2007). Yet, in the case of the CB chocolate, bloom development was higher than EI chocolate samples.…”
Section: Resultsmentioning
confidence: 99%
“…However, β-VI is the most stable polymorph and the transition of β-V to β-VI is one of the important theories in fat bloom formation (Wille and Lutton, 1966;Bricknell and Hartel, 1998;Graef et al, 2005;Khan and Rousseau, 2006). It is known that production parameters and storage conditions, including poor tempering, incorrect cooling methods, presence of soft fats in the centers of chocolates, warm storage conditions, and addition of fats as CBRs, can cause fat bloom formation in the chocolate formulation (Walter and Camillon, 2001;Lonchampt and Hartel, 2006). Due to CB's unique physico-chemical properties, resulting from its symmetrical triacylglycerol species (TAGS, more than 85% of POP, POS and SOS), it is one of the most important ingredients in chocolate formulations (Foubert et al, 2003;Khan and Rousseau, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…[27] Water activity of the chocolates was measured using a Lab-Master a w (Novasina, Switzerland) according to the method used by Konar. [15] a w values of each sample were measured in triplicate 24 h after sample preparation.…”
Section: Melting Propertiesmentioning
confidence: 99%
“…Fat bloom frequently occurs when chocolate is stored over a long period at an elevated temperature (Sonwai and Rousseau, 2006) or when optimal tempering was not applied during the production of the chocolate (Lonchampt and Hartel, 2006). Two types of fat bloom are well known, depending on whether chocolate includes an oily filling in it (filling chocolate) or not (chocolate bar), as depicted in Figure 1.15.…”
Section: Fat Bloom Problemsmentioning
confidence: 99%